First principles calculations of alloying element diffusion coefficients in Ni using the five-frequency model - 吴琼 李树索 马岳 宫声凯 (Chinese physics B, 2012)
The diffusion coefficients of several alloying elements（Al,Mo,Co,Ta,Ru,W,Cr,Re） in Ni are directly calculated using the five-frequency model and the first principles density functional theory.The correlation factors provided by the five-frequency model are explicitly calculated.The calculated diffusion coefficients show their excellent agreement with the available experimental data.Both the diffusion pre-factor（D 0） and the activation energy（Q） of impurity diffusion are obtained.The diffusion coefficients above 700 K are sorted in the following order：DAl〉DCr〉DCo〉DTa〉DMo〉DRu〉DW〉D Re.It is found that there is a positive correlation between the atomic radius of the solute and the jump energy of Ni that results in the rotation of the solute-vacancy pair（E 1）.The value of E 2-E 1（E 2 is the solute diffusion energy） and the correlation factor each also show a positive correlation.The larger atoms in the same series have lower diffusion activation energies and faster diffusion coefficients.